Shocks Affecting the Behavior of Health Expenditure Variables - Salehzadeh, Tooran; Akbari Moghaddam, Beitollah; Mirzapour, Akbar; Hadizadeh, Arash (Business, Marketing, and Finance Open, 2026)
The rapid growth of health-care costs has become one of the main challenges to the sustainability of public finances worldwide. The persistent rise in health-care expenditure and concerns about its long-term fiscal sustainability highlight for policy-makers the need to design effective cost-containment strategies. To this end, identifying the shocks that determine the growth of health-care expenditure and measuring their magnitude constitutes the first and most important step in containing the growth of health-care costs. Therefore, the main aim of this study is to examine the dynamic relationship among health expenditure, economic growth, and total factor productivity (TFP) across the provinces of Iran. This research is causal-comparative and belongs to the category of descriptive-correlational studies. To probe dynamic relationships and to observe the behavior of the study variables in response to shocks originating from other variables, a panel vector autoregression (PVAR) model was employed over the period 2001–2019. Total factor productivity was calculated using the Solow residual method. The impulse-response functions indicate that a GDP shock induces a positive and oscillating response of health expenditure and TFP to that shock. Likewise, a TFP shock induces a positive response of GDP and health expenditure to that shock. Variance decomposition of health expenditure shows that changes in this variable over a ten-year horizon are driven by total factor productivity, the inflation rate, GDP, and education.